Staphylococcus Equorum Isolated from Seabed as Potential Biotool to Cr(Vi) Remediation - Tello-Reyes, M (2013)
Cr(VI) is frequently used in several industrial activities, due to its uncontrolled spill this contaminant has generated serious damage to the environment: chromium hexavalent has a high oxidation potential and is able to go through biological membranes. As consequence Cr(VI)is described as a persistent contaminant with a high toxicity. It has been searched for alternative methods to remediate or detoxify environments contaminated with Cr(VI). The use of microorganisms able to absorb or reduce this type of contaminant is discerned as a potential biotool for remediation of metals-enriched industrial wastes. In order to isolate and identify environmental microorganisms with this capacity, we isolated a bacterium named LMA-2 with a selective pressure of 60 mM of Cr(VI) from contaminated marine sediment. In the morphologic analysis, this marine microorganism evidenced that corresponds to a Gram-positive cocci. This resistant bacterium has a minimal inhibitory concentration for Cr(VI) of 750 mM. The characterization and identification of this strain was made through 16S ribosomal RNA gene, this result revealed that it corresponds to Staphylococcus equorum. Assays using atomic absorption spectrophotometer (AAS) shows that this strain is able to ireduce the concentration of soluble Cr(VI) The capacity of this strain to remediate Cr(VI) was determined in 142.8 mg/L at 10 h of exposition. Our results showed the high resistance and the ability for Cr(VI) remediation by S. equorum. These results suggest that this marine bacterium could be a prospect for future use as a biofilter for seabed marine environment decontamination. © (2013) Trans Tech Publications, Switzerland.